Biophysical and biochemical constraints imposed by salt stress:Learning from halophyte - Bernardo eDuarte; Noomene eSleimi; Isabel eCaçador (Frontiers in Plant Science, 2014)
Soil salinization is one of the most important factors impacting plant productivity. About 3.6 billion of the world’s 5.2 billion ha of agricultural dryland have already suffered erosion, degradation and salinization. Halophytes typically are considered as plants able to complete their life cycle in environments where the salt concentration is 200 mM NaCl or higher. Different strategies are known to overcome salt stress, as adaptation mechanisms from this type of plants. Salinity adjustment is a complex phenomenon characterized by both biochemical and biophysical adaptations. As photosynthesis is a prerequisite for biomass production, halophytes adapted their electronic transduction pathways and the entire energetic metabolism to overcome the salt excess. The maintenance of ionic homeostasis is in the basis of all cellular stress in particular in terms of redox potential and energy transduction. In the present work the biophysical mechanisms underlying energy capture and transduction in halophytes are discussed alongside with their relation to biochemical mechanisms, integrating data from photosystem light harvesting complexes, electronic transport chains to the quinone pools, carbon harvesting and energy dissipation metabolism.